Arterial Stiffening With Exercise in Patients With Heart Failure and Preserved Ejection Fraction - Reddy, Yogesh N V; Andersen, Mads J; Obokata, Masaru; Koepp, Katlyn E; Kane, Garvan C; Melenovsky, Vojtech; Olson, Thomas P; Borlaug, Barry A (Journal of the American College of Cardiology, 2017)
BACKGROUND: Aortic stiffening and reduced nitric oxide (NO) availability may contribute to the pathophysiology of heart failure with preserved ejection fraction (HFpEF). OBJECTIVES: This study compared indices of arterial stiffness at rest and during exercise in subjects with HFpEF and hypertensive control subjects to examine their relationships to cardiac hemodynamics and determine whether exertional arterial stiffening can be mitigated by inorganic nitrite. METHODS: A total of 22 hypertensive control subjects and 98 HFpEF subjects underwent hemodynamic exercise testing with simultaneous expired gas analysis to measure oxygen consumption. Invasively measured radial artery pressure waveforms were converted to central aortic waveforms by transfer function to assess integrated measures of pulsatile aortic load, including arterial compliance, resistance, elastance, and wave reflection. RESULTS: Arterial load and wave reflections in HFpEF were similar to those in control subjects at rest. During submaximal exercise, HFpEF subjects displayed reduced total arterial compliance and higher effective arterial elastance despite similar mean arterial pressures in control subjects. This was directly correlated with higher ventricular filling pressures and depressed cardiac output reserve (both p < 0.0001). With peak exercise, increased wave reflections, impaired compliance, and increased resistance and elastance were observed in subjects with HFpEF. A subset of HFpEF subjects (n = 52) received sodium nitrite or placebo therapy in a 1:1 double-blind, randomized fashion. Compared to placebo, nitrite decreased aortic wave reflections at rest and improved arterial compliance and elastance and central hemodynamics during exercise. CONCLUSIONS: Abnormal pulsatile aortic loading during exercise occurs in HFpEF independent of hypertension and is correlated with classical hemodynamic derangements that develop with stress. Inorganic nitrite mitigates arterial stiffening with exercise and improves hemodynamics, indicating that arterial stiffening with exercise is at least partially reversible. Further study is required to test effects of agents that target the NO pathway in reducing arterial stiffness in HFpEF. (Study of Exercise and Heart Function in Patients With Heart Failure and Pulmonary Vascular Disease [EXEC]; NCT01418248. Acute Effects of Inorganic Nitrite on Cardiovascular Hemodynamics in Heart Failure With Preserved Ejection Fraction; NCT01932606. Inhaled Sodium Nitrite on Heart Failure With Preserved Ejection Fraction; NCT02262078).
Keywords: tepový objem; zátěžový test; Rest; Humans; Heart Failure; Stroke Volume; srdeční selhání; lidé středního věku; funkce levé komory srdeční; HFpEF; dusičnany; Double-Blind Method; Female; Aged; aortic stiffness; senioři; dvojitá slepá metoda; lidé; Exercise Test; hypertension; heart failure; ženské pohlaví; Male; Middle Aged; odpočinek; Nitrates; Exercise; Vascular Stiffness; mužské pohlaví; prospektivní studie; cvičení; exercise; Ventricular Function, Left; tuhost cévní stěny; Prospective Studies